Spiritualitas Seorang Pemimpin Kristen (Implikasi Kitab Nemia) - Esterani, Esterani; Theodorus, Theodorus; Resti, Resti; Weldy, Weldy; Dandi, Dandi (Neolectura, 2024)
Leadership is a familiar topic of discussion. In this era of globalization, leadership has increasingly become a subject of human attention. Numerous pieces of literature on leadership can be found, and seminars, workshops, and meetings discussing leadership are held everywhere. This shows that today, people place significant emphasis on leadership. Leadership is a determining factor in the success or failure of achieving goals in any community. The church, as a community, also recognizes the importance of leadership in achieving its objectives. The accomplishment of goals is closely tied to the role of a leader. Therefore, specific qualifications are needed for a Christian leader. One essential qualification for a Christian leader is spiritual qualification. This journal discusses the spiritual qualifications of a Christian leader, drawing implications from the Book of Nehemiah. One of the key factors contributing to Nehemiah's success in leadership was his spirituality.